2016
DOI: 10.1186/s12864-016-2601-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci identified for blood chemistry components of an advanced intercross line of chickens under heat stress

Abstract: BackgroundHeat stress in poultry results in considerable economic losses and is a concern for both animal health and welfare. Physiological changes occur during periods of heat stress, including changes in blood chemistry components. A highly advanced intercross line, created from a broiler (heat susceptible) by Fayoumi (heat resistant) cross, was exposed to daily heat cycles for seven days starting at 22 days of age. Blood components measured pre-heat treatment and on the seventh day of heat treatment include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 66 publications
3
23
0
Order By: Relevance
“…In order to identify the SNPs within the windows most probably linked to the QTL, we selected those with highest model frequency (Table 2 ), as adopted by Van Goor et al . 19 , 20 . The characterization of those SNPs including their effect, frequency in the population and frequency in the founder lines (TT and CC) is available in Supplementary Spreadsheet S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to identify the SNPs within the windows most probably linked to the QTL, we selected those with highest model frequency (Table 2 ), as adopted by Van Goor et al . 19 , 20 . The characterization of those SNPs including their effect, frequency in the population and frequency in the founder lines (TT and CC) is available in Supplementary Spreadsheet S1 .…”
Section: Resultsmentioning
confidence: 99%
“…A map file was used to position the SNPs into 943 non-overlapping windows of 1 Mb. We adopted 1 Mb non-overlapping windows in our study in agreement with other recent GWAS studies in chickens reported in the literature using genomic prediction methodology 19 , 20 , 78 , 79 . Many SNPs were fitted simultaneously in the model and due to high linkage disequilibrium, the QTL effect can be distributed across these markers 18 , and these previous studies showed that the 1 Mb windows can capture the effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Goor et al used an AIL developed from broiler and Fayoumi to identify quantitative trait loci for body temperature, production traits and blood chemistry under heat stress [8, 18]. We compared Fayoumi in heat stress to broiler under heat stress after contrasting each line’s heat treatment group against the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 distinct genetic lines maintained at Iowa State University that were used in this study were a heat-susceptible broiler line, the heat-resistant Fayoumi, and the F 19 generation of a highly advanced intercross line (AIL) between the broiler and Fayoumi [8, 18]. The Fayoumi line originated from a hot climate (desert region of Egypt) and has not undergone selection for production traits.…”
Section: Methodsmentioning
confidence: 99%